2022
DOI: 10.1007/s13593-022-00781-9
|View full text |Cite
|
Sign up to set email alerts
|

Homegarden agroforestry systems in achievement of Sustainable Development Goals. A review

Abstract: Homegarden, a type of agroforestry system, is one of the earliest thriving traditional food systems reported. Studying the contribution of homegardens in the context of Sustainable Development Goals (SDGs) is crucial when the COVID-19 pandemic has hindered the achievement of many of the crucial SDGs. In this review, we focused on 94 peer-reviewed papers on homegardens from 2010 to 2021 to interrelate them with the corresponding targets and indicators of each SDG. The SDGs were classified into five categories, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 134 publications
0
16
0
Order By: Relevance
“…Kumar (2011) in the previously mentioned study also reported average aboveground standing stocks of C in the range of 16-36 Mg ha -1 for trees in the size class above 20 cm GBH, which is broadly consistent with the present observations. The high biomass C stocks indicate the potential of HGs in climate change mitigation strategies (e.g., SDG-13; Sharma et al 2022)…”
Section: Homegardens For Climate Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar (2011) in the previously mentioned study also reported average aboveground standing stocks of C in the range of 16-36 Mg ha -1 for trees in the size class above 20 cm GBH, which is broadly consistent with the present observations. The high biomass C stocks indicate the potential of HGs in climate change mitigation strategies (e.g., SDG-13; Sharma et al 2022)…”
Section: Homegardens For Climate Actionmentioning
confidence: 99%
“…HGs provide food and nutritional security to the gardeners and represent Nature-based Solutions (NbS) for climate change mitigation and biodiversity conservation. Indeed, they provide an effective framework fundamental to C cycle regulation and agrobiodiversity conservation with enormous potential for achieving the United Nations Sustainable Development Goals (SDGs: Sharma et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on traditional homegardens are often related to agriculture, ecology, nutrition, botany, and many other fields [ 8 ]. Plant diversity, an important core component of homegarden ecology and function, is also the focus of many researchers [ 9 ]. Homegarden plants are plants with certain functions purposely preserved or cultivated in homegardens [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, since rural homegarden system have been planted by combination of annual and perennial plants, consist of three, shrubs, vines, and herbaceous species, often in association with livestock, including native chickens, sheep, goats and cows. As a result, the homegardens have various some socio-economic and cultural, and ecological functions, including medicinal, food, ornamental, spiritual wellbeing, fodder, fuelwood; and carbon sequestration in trees and soil, maintaining soil fertility, soil erosion control, and biodiversity conservation (Iskandar et al, 2018;Agustina et al, 2019;Castaneda-Navarrette, 2021;Rachman et al, 2021;Getachew et al, 2022;Sharma et al, 2022;Suwartapradja et al, 2023).…”
Section: Introductionmentioning
confidence: 99%